التنويع الاقتصادي في الاقتصاد الليبي : الواقع الحالي والإستراتيجية المطلوبة (*) - حمد الفارسي أ.د. عيسى (Scientific Journal of University of Benghazi, 2026)
The policy of economic diversity represents one of the important tools in the process of continuous economic development. It is one of the major challenges that faces the Libyan economy that depends on exporting single depleted commodity which is petrol whose revenues are subjected to fluctuations and saying in the international markets, consequently it cannot be relied on to build the process of continuous development.